The Role of Complexity for Bank Risk during the Financial Crisis: Evidence from a Novel Dataset - Thomas Krause; Talina Sondershaus; Lena Tonzer (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2016)
We construct a novel dataset to measure banks' complexity and relate it to banks' riskiness. The sample covers stock listed Euro area banks from 2007 to 2014. Bank stability is significantly affected by complexity, whereas the direction of the effect differs across complexity measures. This heterogeneity advises against the use of a single complexity measure when evaluating the implications of bank complexity.
urn:nbn:de:gbv:3:2-54641
Keywords: G01; G20; G33; 330; bank risk; complexity; globalization